2014
DOI: 10.1007/s12928-014-0309-x
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of bare-metal stenting after primary stenting for ST-segment elevated myocardial infarctions in the drug-eluting stent era: a propensity score-matched comparison with sirolimus-eluting stent

Abstract: We performed a propensity score-matching comparison of the midterm clinical and angiographic outcomes after primary stenting between using bare-metal stents (BMSs) and sirolimus-eluting stent (SES; Cypher Bx Velocity) for ST-segment elevated myocardial infarction (STEMI), because, in the drug-eluting stent era, the indication of the BMSs when a large balloon diameter is required remained to be controversial. This was a single-center, nonrandomized, retrospective study investigated in October 2013 by enrolling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The present mean balloon diameter of the stent (near 3.50 mm) and postprocedural reference diameter (≥ 3.10 mm) indicated that large vessels were treated in the present cohort because the frequency of TLR after a bare-metal stent (BMS) was relatively low in these baselines. [21][22][23][24] Considering this background, the present study showed far better angiographic outcomes for BES compared to SES, because SES showed a prominent advantage for angiographic outcomes in large vessels compared to the contemporary BMS 23) and zotarolimus-eluting stent, 24) and because angiographic efficacy was equal in large vessels between SES and EES in terms of target vessel failure. 23) Accordingly, the present study is the first to show the efficacy of BES on midterm angiographic outcomes compared to SES after being used in a clinical setting.…”
Section: Discussionmentioning
confidence: 55%
“…The present mean balloon diameter of the stent (near 3.50 mm) and postprocedural reference diameter (≥ 3.10 mm) indicated that large vessels were treated in the present cohort because the frequency of TLR after a bare-metal stent (BMS) was relatively low in these baselines. [21][22][23][24] Considering this background, the present study showed far better angiographic outcomes for BES compared to SES, because SES showed a prominent advantage for angiographic outcomes in large vessels compared to the contemporary BMS 23) and zotarolimus-eluting stent, 24) and because angiographic efficacy was equal in large vessels between SES and EES in terms of target vessel failure. 23) Accordingly, the present study is the first to show the efficacy of BES on midterm angiographic outcomes compared to SES after being used in a clinical setting.…”
Section: Discussionmentioning
confidence: 55%
“…Concerning about the outcomes after primary stenting for patients with STEMI, we previously reported the long-term clinical and angiographic outcomes of BMS vs. SES [1,4], and SES vs. PES [10]. The frequencies of severe cardiac event were statistically equivalent in each paper.…”
Section: Discussionmentioning
confidence: 97%
“…Periprocedural anti-platelet therapy was administered as previously reported [1,4]. In the emergency care unit before primary percutaneous coronary intervention (PCI) was performed, aspirin (162-200 mg) and ticlopidine (200 mg) or clopidogrel (300 mg) was immediately administered orally.…”
Section: Anti-platelet Therapymentioning
confidence: 99%
See 2 more Smart Citations